Pancasila As the Basis of Tax Law and Self Assessment in Income Tax - Wiwi Yuhaeni (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Tax law is one of the positive laws in Indonesia. In practice, is this tax law based on Pancasila? Likewise, is the self assessment system in income tax based on Pancasila? In Indonesia, especially in the city of Bandung Cicadas Pratama Tax Service Office, especially for individual taxpayers, there are still taxpayers who do not submit annual notification letters or do not submit their tax obligations. This situation is certainly contrary to the precepts of Pancasila which is the basis of the philosophy of life of the Indonesian nation. The recearch method uses a descriptive analytical research specification, the approach method is a normative judicial approach. The research stage includes library research which is secondary data as well as field research is primary data and the last is qualitative juridical data analysis. In conclusion, tax law is still based on Pancasila. Pancasila is the philosophy of tax collection. Tax collection must be based on the law. With the collection of taxes, the government must provide good reciprocal service to the community (taxpayers) because they have served the state, namely “paying taxes”. As well as in the self assessment of the income tax system that Pancasila is still the basis of its philosophy. Copliance with personal income tax is very low, especially in the Bandung Cicadas Pratama Tax Service Office. Copliance with taxpayers will increase income from taxes and is needed for development in realizing a just and prosperous society based on Pancasila and the 1945 Constitution.